2013
DOI: 10.1080/01635581.2013.770043
|View full text |Cite
|
Sign up to set email alerts
|

Multitargeting and Antimetastatic Potentials of Silibinin in Human HepG-2 and PLC/PRF/5 Hepatoma Cells

Abstract: Hepatocellular carcinoma (HCC) is the most common sort of primary liver malignancy with poor prognosis. This study aimed at examining the effects of silibinin (a putative antimetastatic agent) on some transcriptional markers mechanistically related to HCC recurrence and metastasis in HepG-2 [hepatitis B virus (HBV)-negative and P53 intact) and PLC/PRF/5 (HBV-positive and P53 mutated) cells. The expression of 27 genes in response to silibinin was evaluated by real-time RT-PCR. The MMP gelatinolytic assay and mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 65 publications
0
18
0
Order By: Relevance
“…How silibinin induced cell death and associated signal pathway of apoptosis is not clear. Ghasemiet al showed that silibinin had a strong cytotoxic effect on liver cell line (HepG2 and Hep3B) and caused the cells undergo apoptosis (Ghasemi et al, 2013). In a similar study,silibinin had an inhibitory effect on the growth of MCF-7 cells against UV radiation (Noh et al, 2011).…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…How silibinin induced cell death and associated signal pathway of apoptosis is not clear. Ghasemiet al showed that silibinin had a strong cytotoxic effect on liver cell line (HepG2 and Hep3B) and caused the cells undergo apoptosis (Ghasemi et al, 2013). In a similar study,silibinin had an inhibitory effect on the growth of MCF-7 cells against UV radiation (Noh et al, 2011).…”
Section: Discussionmentioning
confidence: 69%
“…Silibinin has introduced with more properties for anticancer application, chemopreventive efficacy and nontoxic roles in humans (Kauntz et al, 2012). General in vitro and in vivo studies demonstrate that the chemoprotective role of silibininaccompanied by cell proliferation, angiogenesis and metastasis in several cancers (Ghasemi et al, 2013). Aim of this study is was to detect that silibinin had a potential inhibitory effect on MCF-7 cells in reducing cell growth and increasing apoptosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…SPINK1 production by hepatocellular cancer cells was increased by lipopolysaccharide, suggesting a role as an acute-phase reactant in HCC (46 ). A more recent study using HepG2 and PLC cells showed that a liver-protective drug, silibilin, reduced SPINK1 expression together with a panel of other genes linked to HCC tumorigenesis (47 ). These results suggest that SPINK1 is a potential target for cancer therapy.…”
Section: Hepatocellular Cancermentioning
confidence: 78%
“…However, in a study by Ghasemi et al it is suggested that silibininis able to suppress the transcriptional levels of CCR7 in HepG-2 and PLC/PRF/5 hepatoma cells 21 . Inour study to investigate the effect of various concentrations of silibinin(0, 50, 75 and 100 μM) on CXCR3, CCR5 and CCR7 genes expression on MDA-MB-231 cell lines after 24, 48 and 72 h, Real-Time PCR was used.…”
Section: Effects Of Silibinin On Cell Proliferationmentioning
confidence: 99%